Reattachment theory : queer cinema of remarriage - Wallace, Lee, 1962- (Camera obscura book., 2020)
"REATTACHMENT THEORY eschews dominant queer critiques of same-sex marriage to examine the varied histories of queer influences on marriage. According to the traditional queer critique, the legalization of same-sex marriage signaled a neoliberal and homonormative assimilation into normative structures of heterosexism and reproductive futurism. Countering this argument, queer film scholar Lee Wallace claims that, since the eighteenth century, marriage has allowed for many queer and non-normative plotlines. In this book, Wallace is more interested in marriage as a narrative-both in how marriage is narrativized, as well as the story of the changing meaning of marriage-than she is in marriage as a legal institution. Drawing on historians of marriage, Wallace traces the iterations of love associated with marriage vows: from obligation or duty, to romance, and finally to intimacy. Historicizing the discourse of intimacy, Wallace claims that the valorization of intimacy across the twentieth century led to an idealization of the couple form, regardless of heterosexual or homosexual affiliation. Furthermore, Wallace draws on twentieth-century formulations of sexual reciprocity and sexual satisfaction regardless of marital status-and their links to the discourses of intimacy-to reveal how these concepts proved flexible enough to include homosexuality. Tracking these changing narratives of marriage throughout the twentieth century, Wallace grounds her analyses in an archive of popular culture films. Using Stanley Cavell's notion that, following the "marriage crisis" created by divorce in the early twentieth century, all marriage is remarriage, Wallace argues that after the advent of same-sex marriage, all marriage is gay marriage. Chapter 1, which doubles as the introduction, lays out the stakes of the project. Chapter 2 examines nineteenth-century literature and early twentieth-century popular culture to reveal the changing story of marriage. Chapter 3 situates the 1936 film Craig's Wife as an anticipation of gay and lesbian alternatives to marriage. Chapter 4 reads Tom Ford's film production of Christopher Isherwood's A Single Man as a means to extend homosexual style as a "brand" of cultural and emotional capital. Chapters 6 and 7 engage directly with Cavell's theory of remarriage as an analytic to examine same-sex marriage. This book will be of interest to students and scholars of queer theory, feminist studies, and film studies"--